Analisis Performa Bluetooth pada Sistem Alarm Pengingat Barang yang Tertinggal dengan Smartphone Android - Rafiqmia Khairuddin Nur Hammam; Hidayat Nur Isnianto; Sri Lestari; Y. Wahyo Setiyono (Jurnal Rekayasa Elektrika, 2021)
Someone sometimes forgets to put their belongings so that they leave them somewhere, it will pose a risk of losing their belongings. To solve this problem, a reminder is needed so that it is expected to minimize the risk of loss. This device implements point-to-point communication from the Bluetooth Low Energy AT-09 transmitter module with Arduino Nano and the receiver module with an Android smartphone. This reminder device will activate an alarm on the Android smartphone application when the two modules are more than 5 meters away. The measured distance is converted from the Received Signal Strength Indicator (RSSI) value received by the smartphone which is affected by obstructions, packet loss, and delay. Based on the test results, at a distance of 5 meters, the system can be connected and work properly, in unobstructed conditions (Line of Sight) or obstructed conditions (Non-Line of Sight). In the blocked condition, it has a packet loss of 1.1% to 4.4%, the received signal strength (RSSI) has decreased the value to a difference of -8 dBm, and the delay time is 2 seconds.